The Jehol diary : Yŏrha ilgi of Pak Chiwŏn (1737-1805) - Pak, Chi-wŏn, 1737-1805 (Global Oriental, 2010)
This is the first translation into English of the eighteenth-century Korean masterpiece entitled Yorha ilgi ('The Jehol Diary') by Pak Chiwon (1737-1805). The original text was written in classical Chinese and is a notoriously difficult work to translate. Contents: Crossing the Yalu River; Tales from Shenjing and Gateways and Garrisons.